FISCAL, ICT, AND TRADE DIMENSIONS OF MALAYSIA’S ECONOMIC DEVELOPMENT - Muhammad Taufik Jefri; Lim , Chee Ann (International Journal of Accounting, Finance and Business, 2025)
This study investigates the relationship between fiscal policy, ICT, and trade dimensions in driving Malaysia’s economic development. Using the Autoregressive Distributed Lag (ARDL) model and annual data from 2001 to 2023, the analysis explores both short-run and long-run relationships among these three key dimensions. The results of the bounds test confirm the presence of a long-run relationship between the variables. In the long run, fiscal expenditure and digital adoption have positive effects on economic growth, while trade openness shows a negative relationship. In the short run, trade remains a major contributor to growth, whereas the benefits of digital adoption progress appear more gradually as the economy adjusts to technological changes. Fiscal spending has a smaller short-term impact but supports growth over time. Overall, the findings suggest that Malaysia’s economic growth is moving toward a more sustainable and balanced path, strengthened by sound fiscal management, digital adoption, and resilient trade strategies.